Bioethical reflections on spirituality: a qualitative study based on five older adult patiens with cancer from Mexico. - Gómez Álvarez, José Enrique (2023)
Problem: What type of spiritual responses are produced in the face of a life-threatening disease such as cancer? The answers can be varied, but what common features are found? Objective To carry out a qualitative exploration of the sense of spirituality in 5 Mexican patients with Cancer. Material: a spirituality scale (validated by judge) from the Spanish Society of Palliative Care (SECPAL) was validated for its application in Mexican patients terminal or not that suffer or suffered of cancer. Method: the questionnaire was administered to five patients with cancer via videoconference, and subsequently transcriptions were made and analyzed using the hermeneutic method. Results: several constants were discovered in all patients, such as the importance of family and couple, affiliation to a religious community and the notion of God's will. Conclusions: the sample allowed us to identify some guidelines that may be beneficial for cancer patients, such as facilitating spiritual connection with other patients and access to religious services.